Corpus-Based Analysis of the Most Frequent Adjective on Covid-19 - Idda Astia; Sofi Yunianti (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2020)
This study aims to investigate the type of adjectives in the most frequent adjectives and also the use of the adjective functions on academic writing about COVID-19. This study was conducted by using a corpus tool named sketchengine. The method of this study was a mixed-method by combining quantitative and qualitative approaches. The source of the data was corpus about COVID-19 academic writing due to the fact that COVID-19 has been the trending topic around the globe and also became an international concern. There were several data collection steps; those were first, knowing the most frequent adjective in the COVID-19 corpus by choosing a wordlist. Second, the data were taken 20 the most frequent adjectives used in COVID-19 corpus because 20 data have already represented the most frequent adjectives. Third, it chose the concordance to comprehend the function of the adjective in the COVID-19 corpus. Fourth, 20 the most frequent adjectives were inputted one at a time on concordance. Fifth, the data were analyzed based on the related theory. Finally, it is inferred that the adjective type on the most frequent adjective is a describing adjective, which has the function to frame the condition, situation and characteristic of the noun on the COVID-19 cases.